The Patients’ Cost Analysis for Eye Care Services: An Investigation in Hospitals of Tehran - Nader Jahanmehr; Soheila Damiri; Fatemeh Zaieri; Farasat Fazli Ouchhesar (Journal of Health Management & Informatics, 2020)
Background:The costs of the eye care services are considered as one of the most important obstacles to timely diagnosis and treatment of eye disorders, but there is  little evidence about patients’ cost for receiving these services. Objective: This paper aimed to investigate the costs paid by patients for eye care services in Tehran hospitals. Methods: 346 patients referring to ophthalmology wards of Tehran's educational hospitals were selected throughconvenient sampling method. The data were extracted through researcher-made checklist and investigating the hospital bills in 2017. Then, they were analyzed using descriptive statistics methods, as well as Mann-Whitney and Kruskal Wallis tests in SPSS 21. Results: The share ofhospital bills, informal payments like bought & brought goods, and non-medical costs were 32.8%, 1.85%, and 66.06%, from the total cost paid by patients, respectively. Further, 10.24%, 83.1%, and 6.85% of medical costs were paid by patients, insurance organizations, and government, respectively. Age (p=0.008), type of basic insurance (p=0.000), and the type of the treated disorder (p=0.000) affected the patients' medical costs. On the other hand, the level of income (p=0.001) and place of residence (p=0.001) variables caused significant differences in the total costs paid by patients. Conclusions: The patients’ out-of-pocket payments for ophthalmology services are evaluated as reasonable. Nevertheless, a large share of the total costs paid by patients was non-medical ones. Improving equity in geographical access to ophthalmology services across regions of the country can reduce non-medical costs and increase the possibility of benefiting from the needed ophthalmology services for all population.